Effects of feeding pomegranate peel silage on feed intake and growth performance of Turkey bred sheep (International Journal of Agricultural Research, Innovation and Technology, 2021)
The experiment was conducted to determine the effects of feeding pomegranate peel silage with beet top silage, wheat straw, alfalfa hay, barley, cotton seed cake and mineral plus on feed intake and growth performance of Turkey bred sheep in research farm of Agriculture Faculty, Kabul University. Twelve, two and half years old turkey bred sheep with (57.240 ± 5.28) kg average initial body weight were used in a completely randomized design (CRD). Animals were caged individually in 3 groups and 4 replications. Groups included in this experiment were, first group (Control) or T1 pomegranate peel silage (PPS) 0%, second group or T2 (5% PPS) or 106 g and third group or T3 (10% PPS) or 211 g. In addition, animals were fed with 633 g barley, 633 g alfalfa hay, 211 g cotton seed cake, 106 g beet top silage, 4 g mineral plus with the same amount and wheat straw for control group or T1, T2 and T3, 528 g, 422 g and 317 g in dry matter (DM) basis, respectively once in a day at around 8 am. According to statistical analysis, there was a highly significant difference between groups in feed intake and significant difference in growth performance of sheep. According to L.S.D test, it was shown that the second group (T2) was better in feed intake and growth performance compared to other groups. The FCR of T1, T2 and T3 were 12.43, 7.88 and 15.13, respectively and the FCE were 8.05, 12.69 and 6.61 in control group, T2 and T3, respectively. Results of this study suggest that feeding (5%) pomegranate peel silage with wheat straw, alfalfa hay, cotton seed cake, barley, beet top silage and mineral plus affects the feed intake and growth performance of Tukey sheep.Int. J. Agril. Res. Innov. Tech. 10(2): 146-154, December 2020